Exploring Perceptions of Machine Translation as a Tool for EFL Learning - Nindya Juwita Utimadini (Jurnal Pendidikan Bahasa, 2023)
This study aspires to make a significant contribution to the world of foreign language learning by exploring the role of MT within the learning process. The Translator Machine is famous among the language learner. Even though many negative attitudes are drawn in accepting the existence of the translator machine, the benefits do prove to exist. The current study will elaborate the actual use based on students’ perception of the tool. As surveyed, the current use of Machine Translation for Academic Purposes and Leisure Purposes differs in terms of frequency and purposes. The study reveals the fact that in the classroom students feels to benefit from MT for understanding text given by the lecturer, achieving better scores in English classroom, and learning specific language skills such as vocabulary skill and grammar skill. As contrast, the language learning carried out in leisure settings is for understanding favorite movies, songs, novels, and communicating in their social media.